PENGGUNAAN MOBIL DALAM PENGANGKUTAN WADAH JENAZAH KE KUBURAN BAGI UMAT HINDU DI BALI - Toya Wisuda, Pande Putu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The ceremony is a tradition that characterizes social behavior and the system of ideas of the Balinese Hindu community. Widely present the ceremony covers the life cycle and various social activities in the life of the Balinese Hindu community. The ceremony has always been an important part of accompanying the Balinese Hindu religious system. Along with the changing times, Balinese Hindus have arranged and used time in a strict manner because the activities carried out were more complex. The more complex the activities carried out, the idea of conducting cremation rituals, especially when transporting bodies to the grave in a more efficient way. Traditionally in the past the Ngaben ritual was carried out with a sense of togetherness, help, and religious solidarity that was quite high. However at this time the transfer of bodies to graves has begun to change, using transportation in the form of acar.The phenomenon of transporting the remains to the grave by car is quite interesting to be excavated and disclosed. There are several reasons for transporting the corpse to a grave by car, namely efficiency, distant graveyard and the use of transportation technology. Instead, the implications are the implications of modernization, the implications of weakening tradition, the implications of fading social solidarity, and the implications of education.